2013
DOI: 10.1002/jmv.23797
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of rotavirus strains circulating in Northern Brazil after introduction of a rotavirus vaccine: High prevalence of G3P[6] genotype

Abstract: Rotavirus A (RVA) is the most common cause of severe acute gastroenteritis in infants and young children worldwide, causing 453,000 deaths annually. In Brazil, the most frequent genotype identified was G1 during almost three decades in the pre-vaccination period; however, after anti-rotavirus vaccine introduction, there was a predominance of G2 genotype. The aim of this study was to determine the G and P genotypes of rotaviruses isolated from children under 5 years of age with acute gastroenteritis in the Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
(65 reference statements)
6
28
0
3
Order By: Relevance
“…Despite the high number of different G and P types, the current study showed that 90% of the rotavirus strains belonged to one of the five most common G types (G1, G2, G3, G4, and G9), and 97.5% belonged to one of the two main P types (P[8] and P[4]). Consistent with our data, the genotyping of rotavirus strains from different countries has indicated that more than 85% of strains can be classified into these five G types and three P types (P[8], P[4], and P[6]) . In addition to these common genotypes, which accounted for the majority of the isolates, 21.5% of the isolates were classified into 20 different uncommon types, and about 1% of the isolates carried mixed genotypes.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the high number of different G and P types, the current study showed that 90% of the rotavirus strains belonged to one of the five most common G types (G1, G2, G3, G4, and G9), and 97.5% belonged to one of the two main P types (P[8] and P[4]). Consistent with our data, the genotyping of rotavirus strains from different countries has indicated that more than 85% of strains can be classified into these five G types and three P types (P[8], P[4], and P[6]) . In addition to these common genotypes, which accounted for the majority of the isolates, 21.5% of the isolates were classified into 20 different uncommon types, and about 1% of the isolates carried mixed genotypes.…”
Section: Discussionsupporting
confidence: 88%
“…Noteworthy, among the human G11 strains analyzed to date by whole-genome sequencing, most of the genes of the G11P[6] strain were closely related to those of porcine, human-porcine or bovine-porcine reassortant strains . Recently, a G3P[6] genotype strain was detected in humans at Amazonas and Acre states only (da Silva Soares et al, 2014). In Latin America, G3P[6] strains were detected at a frequency of 0.2% in humans with RVA infections (Linhares et al, 2011), allowing them to be considered a genotype found rarely in humans and never before described in Brazilian pigs.…”
Section: Discussionmentioning
confidence: 97%
“…G2P [4] has been the most common genotype detected in Brazil after the onset of RV1 mass vaccination (Gurgel et al, 2007;de Oliveira et al, 2008;Nakagomi et al, 2008;Leite et al, 2008;Carvalho-Costa et al, 2009da Silva Soares et al, 2014). The emergence of this genotype has motivated a great discussion and a relationship between this phenomenon and RV1 vaccination has been proposed suggesting that universal vaccination would have exerted selective pressure on circulating RVAs, selecting G2P [4] (Gurgel et al, 2007;Nakagomi et al, 2008;.…”
Section: Discussionmentioning
confidence: 98%